PEMINDAH TANGANAN TANPA IZIN JAMINAN FIDUSIA MENURUT UNDANG - UNDANG NOMOR 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA DI POLRES SUKOHARJO - Samudra Adi Wijaya; Hadi Mahmud; Nourma Dewi (Media Bina Ilmiah, 2024)
The purpose of this study is to determine the implementation of the law against embezzlement of fiduciary guarantees in accordance with the provisions in Law Number 42 of 1999 concerning Fiduciary Guarantees and obstacles to law enforcement against unauthorised transfer of fiduciary guarantees at Sukoharjo Police Station. The method used is empirical juridical approach. The approach to the problem studied by using Law No. 42 of 1999 concerning fiduciary guarantees as well as a direct approach from the field by involving data obtained directly from respondents and research location sources related to unauthorised transfer of fiduciary guarantees in the Sukoharjo Regency area. Financing institutions as creditors need to register fiduciary guarantees with the fiduciary registration office by including a clause that the debtor is prohibited from transferring, mortgaging, leasing goods that are objects of collateral without the knowledge of the creditor. It is necessary to reform Law No. 42/1999 on Fiduciary Guarantee by including Restorative Justice as an alternative to resolving cases of embezzlement / transfer of fiduciary security objects for the sake of legal certainty, justice and benefit for the community.